New transition of digital music copyright protection in China: A case study of Jay Chou’s model / Du Lei - Du, Lei (2017)
Jay Chou is one of the most well-known pop singers not only in China but also among the overseas Chinese communities. He created a digital album - Aiyo Bu Cuo known as Jay Chou’s Model was released in 2014. Digital album requires payment for downloading the copyrighted music through authorized websites. Unlike physical CDs, the music of the digital album was stored in digital format and transmitted through the Internet. In this research, Jay Chou’s model that published in 2014 will be studied. On the basis of the digital album Jay Chou’s model, this research will analyze the changes in digital music market in China, regarding the protection measures, business model and the improvement in the future. Firstly, Chapter 1 will present an overview of the digital music and related issues about copyright by focusing on the definition and issues related to the digital music industry, music copyright and digital music copyright in China. Chapter 2 will present literatures of history of Chinese digital copyright and development of Chinese music industry, Digital Millennium Copyright Act, revenue model in worldwide applied into business model of digital music. Chapter 3 will present methodology of this research. Secondly, Chapter 4 will analyze evolution of digital music industry in China 2009-2014, chain reaction and influence of Jay Chou’s model, business model and SWOT of digital music in China. rdly, based on the market status, it will take consideration the protection measures with data chart analysis, discuss the operation of digital album model and put forward some suggestions in Chapter 5.